Combination of In Silico Methods in the Search for Potential CD4+ and CD8+ T Cell Epitopes in the Proteome of Leishmania braziliensis - e Silva, Rafael de Freitas; Ferreira, Luiz Felipe Gomes Rebello; Hernandes, Marcelo Zaldini; de Brito, Maria Edileuza Felinto; de Oliveira, Beatriz Coutinho; da Silva, Ailton Alvaro; de-Melo-Neto, Osvaldo Pompílio; Rezende, Antônio Mauro; Pereira, Valéria Rêgo Alves (Frontiers in Immunology, 2016)
The leishmaniasis are neglected tropical diseases widespread throughout the globe which are caused by protozoans from the genus Leishmania and are transmitted by infected phlebotomine flies. The development of a safe and effective vaccine against these diseases has been seen as the best alternative to control and reduce the number of cases. To support vaccine development, this work has applied an in silico approach to search for high potential peptide epitopes able to bind to different Major Histocompatibility Complex Class I and Class II (MHC I and MHC II) molecules from different human populations. First, the predicted proteome of Leishmania braziliensis was compared and analysed by modern linear programs to find epitopes with the capacity to trigger an immune response. This approach resulted in thousands of epitopes derived from 8,000 proteins conserved among different Leishmania species. Epitopes from proteins similar to those found in host species were excluded and epitopes from proteins conserved between different Leishmania species and belonging to surface proteins were preferentially selected. The resulting epitopes were then clustered, to avoid redundancies, resulting in a total of 230 individual epitopes for MHC I and 2,319 for MHC II. These were used for molecular modeling and docking with MHC structures retrieved from the Protein Data Bank (PDB). Molecular docking then ranked epitopes based on their predicted binding affinity to both MHC I and II. Peptides corresponding to the top 10-ranked epitopes were synthesized and evaluated in vitro for their capacity to stimulate PBMC from post-treated cutaneous leishmaniasis patients, with PBMC from healthy donors used as control. From the ten peptides tested, 50% showed to be immunogenic and capable to stimulate the proliferation of lymphocytes from recovered individuals.